2017
DOI: 10.1016/j.jare.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of Bacillus subtilis SPB1 lipopeptides in toothpaste formulation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Bouassida et al . () examined the potential of B. subtilis SPB1 LP in toothpaste formulation and showed that an LP‐based product exhibited an important antimicrobial activity against Enterobacter sp. and S. typhimurium .…”
Section: Health‐related Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouassida et al . () examined the potential of B. subtilis SPB1 LP in toothpaste formulation and showed that an LP‐based product exhibited an important antimicrobial activity against Enterobacter sp. and S. typhimurium .…”
Section: Health‐related Applicationsmentioning
confidence: 99%
“…In their study of the effectiveness of rhamnolipids derived from nonpathogenic Burholderia thailandensis E264, Elshikh et al (2017a) identified a 3-4 log decrease in bacterial viability among oral pathogens (the potential of biosurfactants in oral cavity care has been reviewed in detail by Elshikh et al 2016). Bouassida et al (2017) examined the potential of B. subtilis SPB1 LP in toothpaste formulation and showed that an LP-based product exhibited an important antimicrobial activity against Enterobacter sp. and S. typhimurium.…”
Section: Oral Carementioning
confidence: 99%
“…Produced lipopeptide can be extracted by acid alkali method [10], with phosphate-buffered saline (PBS) [2],by HCl Precipitation[3], [9],centrifugation, filteration [6], [14],acetone precipitation [14].…”
Section: Extraction Methodsmentioning
confidence: 99%
“…After 1945, several formulation advancements of different detergents had begun; sodium lauryl sulfate had been used as emulsifying agent [1]. The first toothpaste was invented by the dental surgeon and chemist Washington Went-worth Sheffield [10]. Sodium lauryl sulphate (SLS) and sodium lauryl sarcosinate are the two most common surface-active agents.…”
Section: A Toothpastementioning
confidence: 99%
See 1 more Smart Citation